Mcp1 and Mcp2, two novel proteins involved in mitochondrial lipid homeostasis - Tan, Tao; Özbalcı, Çağakan; Brügger, Britta; Rapaport, Doron; Dimmer, Kai Stefan (Journal of cell science, 2013)
The yeast mitochondrial outer membrane (MOM) protein Mdm10 is involved in at least three different processes: (1) association of mitochondria with the endoplasmic reticulum and mitochondrial lipid homeostasis (2) membrane assembly of MOM proteins, and (3) inheritance and morphogenesis of mitochondria. To decipher the precise role of Mdm10 in mitochondrial function, we screened for high-copy suppressors of the severe growth defect of the mdm10Δ mutant. We identified two novel mitochondrial proteins (open reading frames YOR228c and YLR253w) that we named Mdm10 complementing protein (Mcp) 1 and Mcp2. Overexpression of Mcp1 or Mcp2 restores the alterations in morphology and stability of respiratory chain complexes of mitochondria devoid of Mdm10, but the observed defect in assembly of MOM proteins is not rescued. Lipid analysis demonstrates that elevated levels of Mcp1 and Mcp2 restore the alterations in mitochondrial phospholipid and ergosterol homeostasis in cells lacking Mdm10. Collectively, this work identifies two novel proteins that play a role in mitochondrial lipid homeostasis and describes a role of Mdm10 in ergosterol trafficking.
Gesehen am 31.01.2022